2014 IEEE Military Communications Conference 2014
DOI: 10.1109/milcom.2014.192
|View full text |Cite
|
Sign up to set email alerts
|

A Load-Based Approach for Selecting the Backbone Terminals for a Hierarchical Ad Hoc Network

Abstract: Efficient routing in mobile ad hoc networks (MANETs) is highly desired and connected dominating sets (CDS) have been gaining significant popularity in this regard. The CDS based approach reduces the search for a minimum cost path between a source and destination terminals to the set of terminals forming the backbone network. Researchers over the years have developed numerous distributed and localized algorithms for constructing CDSs which minimize the number of terminals forming the backbone or which provide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Also, under this network environment conditions, the number of CDS members after performing the Marking process will be compared among the IRCS-CDS, MaxS-CDS and RCDS algorithms. As shown in Figures 29,30, and 31, those can be found that the IRCS-CDS and MaxS-CDS algorithms produce the minimum number of CDS when the Marking procedure is completed.…”
Section: Simulation Results and Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…Also, under this network environment conditions, the number of CDS members after performing the Marking process will be compared among the IRCS-CDS, MaxS-CDS and RCDS algorithms. As shown in Figures 29,30, and 31, those can be found that the IRCS-CDS and MaxS-CDS algorithms produce the minimum number of CDS when the Marking procedure is completed.…”
Section: Simulation Results and Analysismentioning
confidence: 91%
“…The internal network routing scheme for the subnet will be proceeded by itself, and this is the basic cooperating method for the overall hierarchical Internet architecture. Since the hierarchical routing mode can respond to the changes in the network variabilities efficiently, it becomes a widely used network architecture so far [30]. Dominating-Set-Based Routing is one of the most representative algorithms based on the hierarchical routing mode.…”
Section: Routing Protocols For Manetmentioning
confidence: 99%